Do Economists' and Financial Markets' Perspectives on the New Members of the EU differ? - Schadler, Susan; Luengnaruemitchai, Pipat (Washington, D.C. : International Monetary Fund, 2007)
In the past several years, the ten new Central and Eastern European members of the European Union have enjoyed rapid growth but frequently alongside growing external imbalances. Economists have pointed to rising vulnerabilities, but markets compressed sovereign bond yields. This paper examines the evidence from the perspective of economists' vulnerability analysis and markets' pricing of sovereign bonds. It finds that spread are lower than can be explained by "fundamentals" and speculates on the causes and permanence of this yield compression.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet